Βιβλιοκρισία του: J. HALDON, The Palgrave Atlas of Byzantine History, Palgrave, Macmillan, London 2005 - ΛΟΥΓΓΗΣ Tηλέμαχος K. (Byzantina Symmeikta, 2011)
Βιβλιοκρισία του: J. HALDON, The Palgrave Atlas of Byzantine History, Palgrave, Macmillan, London 2005, ISBN 978-0-230-24364-4